Mekanisme Pasar untuk Mencapai Keseimbangan Pasar Dalam Sistem Ekonomi Islam - Adelia, Della; Kustiawati, Dedek; Musyarrofah, Ani; Bina Hakim, Indira (Rifa'Institute, 2023)
A country's economic activity is very dependent on the role of the market, even though injustice and fraud often occur in its trading activities, especially in determining the price offered. Therefore a rule is needed regarding market price determination, where the rule is known as a market mechanism, namely price setting based on demand and supply. The market is where the process of demand and supply occurs until the equilibrium price is reached. This research is a literature research or library reasearch that examines information through books, documents, articles, and other literature media that can be used as a source in preparing a study. This study aims to determine the role of market mechanisms to create market balance in the view of Islamic economics. The results showed that Islam puts the market in an important position in the economy of the market mechanism in accordance with sharia does not promote government intervention in normal market conditions. However, when the market is distorted, it takes the role of the government in overcoming problems to realize the benefits of the people